A word with mother: understanding the form and meaning of occupancy of kangaroo care in method - do Carmo, Rafaela Freires (2018)
The objective of this research was to understand the form and meaning of the occupation of mothers of newborns who were in the second stage of the Kangaroo Method. The study consisted of a qualitative exploratory and descriptive research. It was developed in a Kangaroo Neonatal Intensive Care Unit of a public reference hospital in maternal and child care in the Northern Region of Brazil. Ten mothers of newborns in the second stage of the Kangaroo Method participated in the study. Semi-structured interviews were conducted and thematic content analysis was used as a data-processing strategy. The results were grouped into two categories: 1) On the occupational form: how the Activities of Daily Living (ADLs) of mothers in a Kangaroo ward take place; 2) On the occupational meaning of caring for preterm newborns in a Kangaroo ward. The research made it possible to understand the fears, doubts, expectations, and desires related to the occupation of caring, revealing how the daily activities occur in these conditions. It made it possible to understand the occupational form and meaning of being mothers of premature children and being in a Kangaroo ward.